2020
DOI: 10.1055/s-0039-3402037
|View full text |Cite
|
Sign up to set email alerts
|

Axenfeld-Rieger Anomaly and Neuropsychiatric Problems—More than Meets the Eye

Abstract: Objective The main purpose of this article is to demonstrate the co-occurrence of Axenfeld-Rieger anomaly and neuropsychiatric problems as clinical signs of genetically determined cerebral small vessel disease in two patients. Case Study We report on two adolescent individuals with ocular anterior segment dysgenesis (Axenfeld-Rieger anomaly) presenting with neuropsychiatric symptoms. Both patients underwent cerebral magnetic resonance imaging showing white matter T2-hyperintensities involving differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 22 publications
1
0
0
Order By: Relevance
“…Although white matter abnormalities and atrophy may become apparent with the physiological aging process, the involvement seen in Individual 1 is considerably more extensive and diffuse than what expected at age 59. All these observations are in line with previous reports in which children as young as 1 year-old presented clear CSVD (French et al, 2014) and diffusely extensive white matter abnormalities were found in teenagers (Saffari et al, 2020), thus suggesting that in FOXC1-related disorders age, disease duration, and brain abnormalities are not linearly correlated. Nevertheless, it is worth following patients with regular brain MRI studies.…”
Section: Discussionsupporting
confidence: 92%
“…Although white matter abnormalities and atrophy may become apparent with the physiological aging process, the involvement seen in Individual 1 is considerably more extensive and diffuse than what expected at age 59. All these observations are in line with previous reports in which children as young as 1 year-old presented clear CSVD (French et al, 2014) and diffusely extensive white matter abnormalities were found in teenagers (Saffari et al, 2020), thus suggesting that in FOXC1-related disorders age, disease duration, and brain abnormalities are not linearly correlated. Nevertheless, it is worth following patients with regular brain MRI studies.…”
Section: Discussionsupporting
confidence: 92%